4‐hydroxythiophenol grafted PS‐b‐PAA block copolymers: Preparation and formation of porous and bowl‐shaped assemblies. Issue 16 (13th April 2016) - Li, Wenting; Li, Na; Zhao, Jiaxu; Zhang, Xiaokai; Li, Xue
ABSTRACT: 4‐Hydroxythiophenol (HTP) grafted poly(styrene‐ b ‐acrylic acid) (PS‐ b ‐PAA) block copolymers (BCPs) (PS‐ b ‐PAA‐ g ‐HTP) was synthesized using the esterification reaction between the carboxyl groups and hydroxyl groups. Self‐assembly behavior of the graft copolymer in 1, 4‐dioxane/water was investigated. Assemblies of different morphologies, porous, and bowl‐shaped structures, could be easily prepared. A possible mechanism for the formation of the porous and bowl‐shaped structures was discussed. The present study showed a facile method for the preparation of functionalized PS‐ b ‐PAA BCPs, which could easily self‐assembly into novel structures in aqueous solution. These assemblies may be used to generate new functional materials. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1551–1557 Abstract : 4‐hydroxythiophenol grafted PS‐ b ‐PAA block copolymers were prepared, and porous and bowl‐shaped structures were obtained in aqueous solution.